Physical activity mass media campaigns and their evaluation: a systematic review of the literature 2003–2010 - Leavy, Justine; Bull, F.; Rosenberg, M.; Bauman, A. (Oxford University Press, 2011)
Internationally, mass media campaigns to promote regular moderate-intensity physical activity have increased recently. Evidence of mass media campaign effectiveness exists in other health areas, however the evidence for physical activity is limited. The purpose was to systematically review the literature on physical activity mass media campaigns, 2003–2010. A focus was on reviewing evaluation designs, theory used, formative evaluation, campaign effects and outcomes. Literature was searched resulting in 18 individual adult mass media campaigns, mostly in high-income regions and two in middle-income regions. Designs included: quasi experimental (n = 5); non experimental (n = 12); a mixed methods design (n = 1). One half used formative research. Awareness levels ranged from 17 to 95%. Seven campaigns reported significant increases in physical activity levels. The review found that beyond awareness raising, changes in other outcomes were measured, assessed but reported in varying ways. It highlighted improvements in evaluation, although limited evidence of campaign effects remain. It provides an update on the evaluation methodologies used in the adult literature. We recommend optimal evaluation design should include: (1) formative research to inform theories/frameworks, campaign content and evaluation design; (2) cohort study design with multiple data collection points; (3) sufficient duration; (4) use of validated measures; (5) sufficient evaluation resources.